Investigation of the Genotoxic Potential of the Marine Toxin C17-SAMT Using the In Vivo Comet and Micronucleus Assays - Zeineb Marzougui; Sylvie Huet; Anne-Louise Blier; Ludovic Le Hégarat; Haïfa Tounsi-Kettiti; Riadh Kharrat; Riadh Marrouchi; Valérie Fessard (Marine Drugs, 2022)
The contaminant responsible for the atypical toxicity reported in mussels from Bizerte Lagoon (Northern Tunisia) during the last decade has been characterized as C17-sphinganine analog mycotoxin (C17-SAMT). This neurotoxin showed common mouse toxic symptoms, including flaccid paralysis and severe dyspnea, followed by rapid death. For hazard assessment on human health, in this work we aimed to evaluate the in vivo genotoxic effects of this marine biotoxin using the classical alkaline and modified Fpg comet assays performed to detect DNA breaks and alkali-labile sites as well as oxidized bases. The micronucleus assay was used on bone marrow to detect chromosome and genome damage. C17-SAMT induces a statistically insignificant increase in DNA tail intensity at all doses in the duodenum, and in the spleen contrary to the liver, the percentage of tail DNA increased significantly at the mid dose of 300 µg/kg b.w/d. C17-SAMT did not affect the number of micronuclei in the bone marrow. Microscopic observations of the liver showed an increase in the number of mitosis and hepatocytes’ cytoplasm clarification. At this level of study, we confirm that C17-SAMT induced DNA damage in the liver but there was no evidence of effects causing DNA oxidation or chromosome and genome damage.